Pengaruh Social Media Marketing dan Celebrity Endorser terhadap Keputusan Pembelian pada Produk Skincare Scarlett Whitening : Studi pada Mahasiswa Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar - Fahira Kamilia Salsabila; Burhanuddin Burhanuddin; Muh. Ichwan Musa; Nurul Fadilah Aswar; Ilma Wulansari Hasdiansa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The use of social media and celebrities in marketing strategies has become a significant phenomenon in the beauty industry, including skin care products. This study aims to determine how the influence of social media marketing and celebrity endorsers on purchasing decisions for scarlett whitening skincare products for students of the Management Study Program, Faculty of Economics and Business, Makassar State University. This study uses a quantitative approach and a questionnaire as a data collection instrument. The population in this study were active students of the 2020 batch of Management Study Program, Faculty of Economics and Business, Makassar State University and the sample used was 100 respondents. The analysis technique used is multiple linear regression analysis using Stastical Product and Service Solution (SPSS) version 26. The results of this study indicate that Social Media Marketing and Celebrity Endorser have a positive and significant effect on Purchasing Decisions in Management Study Program students at the Faculty of Economics and Business, Makassar State University.